Decision Making Process of Women Migrant Workers in West Java: The Intertwine of Religion, Culture, and Social Reality - Yeni Huriani; Nablur Rahman Annibras (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
The decision to work abroad is a unique dynamic for women migrant workers because they have to leave their homes for a long time. The choice is not an easy thing to do. For women in West Java, who are predominantly Muslim, leaving their homes is still a theological and cultural debate as to whether women may work outside the home. Culturally, women are “dulang tinande,” in which they are “not as a determinant” in family life. However, data show that high percentage of Sundanese women work abroad. This fenomenon is interested to be investigated. This research uses a feminist approach to uncover women’s experiences and to recognise women’s voices to be heard related to women migrant workers from West Java. Research shows that these workers have three motives for choosing to work abroad, namely: economic, human capital, and social reasons. Besides, they go through four decision-making processes to become migrant workers: self-stabilization, consultation with relatives, seeking information related to employment agencies (PJTKI), and consulting with Muslim clerics to ask for prayer and safety amulets. This study also found some interesting findings regarding women’s decision to work abroad. First, resilient. They have strong mental endurance by taking immeasurable risks to work in another country. Second, a change in gender relations between women migrant workers and their husbands. Interestingly, the shift in gender relations is temporary.